Sunlight photocatalytic performance of Mg-doped nickel ferrite synthesized by a green sol-gel route - Nadumane, Aparna (Elsevier, 2019)
We report an environmentally friendly synthetic strategy to synthesize new nickel ferrite and Mg doped nickel ferrite photocatalysts under modified green sol-gel route in which Aloe Vera gel acts as a natural template. The crystalline phase, surface morphology and size of the prepared photocatalysts were characterized by PXRD, SEM, TEM and HRTEM analysis. The energy band gap of the nanoparticles (NPs) can be tuned in the range of 2.55e2.34 eV by varying the dopant concentration. The photoluminescence analysis indicates that the present NPs are an effective white component in display applications. These synthesized NPs were used for photocatalytic decomposition of recalcitrant pollutants in aqueous media under sunlight irradiation. Among investigated samples, the NiFe2O4: Mg2þ (1 mol %) exhibits the highest photocatalytic efficiency for the decomposition of recalcitrant pollutants, which is higher than that of the commercial P25. This enhancement in photocatalytic performance can be mainly attributed to the balance between the parameters, crystallanity, band gap, morphology, crystallite size, defects, dopant amount and combined facets of photocatalysis. It opens a new window to use this simple greener route to synthesize bi-functional NPs in the area of photocatalysis particularly waste water treatment and display applications